INNOVATIONS AND ADVANCED FOREIGN EXPERIENCES IN TEACHING CONSTRUCTION DRAWINGS IN THE EDUCATION SYSTEM - Latipov Rustam Atakhanovich (Scholar Express Journal, 2022)
The article briefly examines the state of teaching drawing in secondary schools of the country on the example of construction drawing and the level of its compliance with modern requirements. The teaching of construction drawing in foreign countries was analyzed. It was also studied and analyzed the innovations in the teaching of construction drawing and important aspects of advanced foreign experience, innovative approaches to the educational process in them. The results of the analysis show that the science program includes the introduction of students to the professions of architects and builders through the study of construction drawings (vocational work) and teaching them to read simple construction drawings, the effective use of time in graphic exercises and assignments. Tasks designed to develop students ’creative abilities using graphic tools are described.
Keywords: Scale; Facade; Plan; Shear